2022
DOI: 10.5098/hmt.18.10
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance Enhancement of Heat Pipe Heat Exchanger in the Air-Conditioning System by Using Nanofluid

Abstract: To reduce the energy consumption in air-conditioning systems without changing the required temperature level in the air-conditioned space, Heat Pipe Heat Exchanger (HPHE) has been experimentally used and tested. The heat pipe has been filled with working fluid by about 50% of the volume of the evaporator which represents the filling ratio. In this research, three mass concentration of nanoparticle from copper oxide (CuO), 1wt%, 3wt% and 5wt% have been used and studied. Additionally, its effect on the HPHE effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…nuclear reactor [3,11], the ceramic industry [4][5][6]12], solar collector [13,14], coal to liquid process [15,16], HVAC systems [17][18][19][20][21][22], heat recovery system [23][24][25][26][27][28][29], gas city gate station [30], steel industry [31,32], dyeing and printing industry [33], the…”
Section: Wick Heat Pipementioning
confidence: 99%
See 1 more Smart Citation
“…nuclear reactor [3,11], the ceramic industry [4][5][6]12], solar collector [13,14], coal to liquid process [15,16], HVAC systems [17][18][19][20][21][22], heat recovery system [23][24][25][26][27][28][29], gas city gate station [30], steel industry [31,32], dyeing and printing industry [33], the…”
Section: Wick Heat Pipementioning
confidence: 99%
“…nuclear reactor [3,11], the ceramic industry [4][5][6]12], solar collector [13,14], coal to liquid process [15,16], HVAC systems [17][18][19][20][21][22], heat recovery system [23][24][25][26][27][28][29], gas city gate station [30], steel industry [31,32], dyeing and printing industry [33], the solar collector [38][39][40], photovoltaic panel [41], steel industry [42,43] pressure reduction stations [34], heat recovery of coal-fired flue gas [35], aluminum industry [36], combine harvester [37] Flat-plate heat pipe Flat-plate heat pipes typically have thinner cross-sections, making them suitable for heat conduction within limited spaces.…”
Section: Wick Heat Pipementioning
confidence: 99%
“…For the utilization of 5wt% CuO mass concentration while employing approximately 701.023 Watts of pure water in a nanofluid air conditioning system employing a heat exchanger. It conserves more energy than utilizing pure water (Abdallah et al (2022)).…”
Section: Fig 1 the Characteristics Of Rtpct And The Two-phase Flow Pa...mentioning
confidence: 99%
“…Economic analysis showed a downward trend in electricity consumption costs, with a payback period of approximately three years and a service life of 20 years. Furthermore, Abdallah et al [ 14 ] showed that the use of HPHE with the addition of nanofluid and temperature variations increased the effectiveness of the heat pipe by 0.59346–883.284 W at an inlet air temperature of 55 °C and air velocity of 1 m/s. This research shows that the objective of using an HPHE in HVAC systems has not been in-depth on the prototype of the room.…”
Section: Introductionmentioning
confidence: 99%